Reflexions on number concordance in complex Nominal Syntagms (SNs) in Angolan Portuguese (PA) - Pinto, Hermenegildo; Pessela, Jeremias (Universidade Estadual Paulista, 2021)
This paper aims to describe the phenomenon of number agreement in complex DPs that perform the syntactic function of the direct object of the sentence, in Angolan students, bilingual with Portuguese L1 and Bantu L2, or vice versa. We also intend to evaluate the treatment given to the phenomenon of concordance in the DPs, from the point of view of teaching and learning. The study is based on linguistic variation and language learning teaching theories, as they offer explanations for the occurrence of deviations in the acquisition of non-native languages. The search type is mixed. The published data indicate that Angolan students use a mixed agreement mechanism in DPs that have to their left core words of categories defined as definite articles, numerals and quantifiers. In these cases, the plural is marked as elements and not in the noun. Furthermore, the fact that in the normative documents of the process of teaching and learning of Portuguese does not consider aspects of the contact of Portuguese with the Bantu languages spoken in Angola, difficulty in correctly appropriating agreement mechanisms.